2005
DOI: 10.1111/j.1540-8191.2005.0155a.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic and Hemodynamic Follow-Up of Patients After Partial Left Ventriculectomy

Abstract: Angiographic, Doppler-echocardiographic and hemodynamic studies early (+6 days) and late (+180 days) after partial left ventriculectomy (PLV) on 24 patients revealed that PLV decreased end-systolic volume (or dimension) more than the end-diastolic volume (or dimension), improving stroke volumes (or contractile excursion), and doubling ejection fraction (or fractional shortening). Results of PLV appeared to depend on a balance between improved systolic contractility and reduced diastolic performance. All these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Partial left ventriculectomy has been virtually abandoned, largely because of the unpredictability of the results compared with the morbidity and mortality associated with the procedure. It has been reported that hospital survival after this procedure is 83%,9 and 10‐year survival is only 16% (Sinisa Gradinac, personal communication). In surviving patients, improvement in symptomatic status, functional capacity, and LV haemodynamics were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Partial left ventriculectomy has been virtually abandoned, largely because of the unpredictability of the results compared with the morbidity and mortality associated with the procedure. It has been reported that hospital survival after this procedure is 83%,9 and 10‐year survival is only 16% (Sinisa Gradinac, personal communication). In surviving patients, improvement in symptomatic status, functional capacity, and LV haemodynamics were noted.…”
Section: Discussionmentioning
confidence: 99%
“…SPECT further demonstrated that the volume of the surgical scar did not increase from 3 to 12 months postoperatively. Kawaguchi et al found that on post-PLV follow up, LVESV and LVESD were decreased more than the LVEDV and LVEDD [6]. This could explain the observed improvement in LVSV, contractile excursion, LVEF and LV fractional shortening.…”
Section: Changes In Haemodynamic and Cardiac Variables After Svrmentioning
confidence: 69%
“…The early experience of surgical treatment in patients with Chagas cardiomyopathy comes from Brazil, where Dr. Batista and his team performed numerous operations in this patient population. At that time, surgical ventricular restoration with ventriculectomy was the mainstay of surgical therapy for dilated cardiomyopathy secondary to Chagas disease, especially in patients who were not candidates or had no access to transplant centers . The Batista operation was performed in Chagas patients with dilated cardiomyopathy in an effort to restore ventricular geometry and function.…”
Section: Introductionmentioning
confidence: 99%